1984
DOI: 10.1093/nar/12.18.6951
|View full text |Cite
|
Sign up to set email alerts
|

Post-transcriptional regulation of glyceraldehyde-3-phosphate-dehydrogenase gene expression in rat tissues

Abstract: We have isolated and identified cDNA clones containing part of the coding sequence for rat glyceraldehyde-3-phosphate-dehydrogenase (GAPDH, E.C. 1.2.1.12). By using one of these clones as a probe, we have shown that: i) the abundance of GAPDH mRNA is different in various tissues of the adult rat and in good correlation with the abundance of the enzyme; ii) the transcription rates are quite similar in all tissues tested. We therefore conclude that the tissue-specific differential GAPDH gene expression is regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
211
2

Year Published

1988
1988
2005
2005

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 453 publications
(220 citation statements)
references
References 32 publications
7
211
2
Order By: Relevance
“…It seems more probable that regulation was occurring at the translational level or subsequent to it in these tissues, a result in keeping with the preliminary observations of Piechaczyk et al [7] on LDH A mRNA levels in a number of different rat tissues. The nature of this regulatory process remains quite unknown at the present time.…”
Section: Discussionsupporting
confidence: 82%
“…It seems more probable that regulation was occurring at the translational level or subsequent to it in these tissues, a result in keeping with the preliminary observations of Piechaczyk et al [7] on LDH A mRNA levels in a number of different rat tissues. The nature of this regulatory process remains quite unknown at the present time.…”
Section: Discussionsupporting
confidence: 82%
“…As early as 1975, 18S rRNA was reported to increase in expression with cytomegalovirus infection. 12 In 1984, Piechaczyk et al 13 reported that while GAPDH transcription occurred at a similar rate in different rat tissues, they contained very different amounts of mRNA. In 1985, HPRT was reported to be constitutively expressed at low levels in most human tissues but was elevated in certain parts of the central nervous system 14 and in 1987 b-actin mRNA was reported to be differentially expressed in different leukaemia patient tumour samples.…”
Section: Normalisation; Reference Genesmentioning
confidence: 99%
“…The filters were exposed overnight using X-Omat XAR film (Kodak) at k70 mC. Filters were also probed with a mouse MT-I probe [22] and a glyceraldehyde-3-phosphate dehydrogenase cDNA clone [23].…”
Section: Rna Isolation and Northern Blotsmentioning
confidence: 99%